Developing Progressive Islamic Aqidah Teaching Materials for Middle School Students - Romadlon, Dzulfikar Akbar; Istikomah, Istikomah; Haryanto, Budi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research will develop teaching materials for aqidah from the perspective of the